Progress of the Composition, Biological Activity and Extraction Technology of Sweet Potato Protein and Peptide - Wei XU; Qingfu KONG; Xueqiang WANG; Guanghua LI; Lizeng PENG; Chune PENG (Shipin gongye ke-ji)
Sweet potato is an important crop, and rich in protein and peptide which have great development potential. Sweet potato protein mainly includes dominant storage protein and small amount glycoprotein, different molecular weight sweet potato peptide can be obtained from protein by enzymatic or chemical hydrolysis. Sweet potato protein and peptide contain 18 types of amino acids that are essential for human body, and its diverse composition of amino acids provides unique nutritional value and its biological activity possess prominent role in the prevention and treatment of cancer, hypertension, obesity and other diseases. Sweet potato is usually used to produce starch, vermicellis and other foods, whereas, huge wastewater was produced during the production process, causing environmental pollution and wastage of protein resource. Therefore, the extraction and application of sweet potato protein from waste water is crucial. Currently, effective extraction and purification methods of sweet potato protein and peptide are commonly used, such as alkaline extraction and acid precipitation, enzymatic digestion, ultrafiltration and so on, but still need optimization and innovation to improve the extraction rate and purity to meet the needs of various fields. Future research can combine modern biotechnology and information technology to study the structure-function relationship, and explore more biological activities and application potentials of sweet potato protein and peptide. The current research status of sweet potato protein and peptide are reviewed in terms of structure composition, physicochemical properties, extraction, purification and biological activity in this paper. This review provides a reliable basis for the industrial production of sweet potato protein and peptide, and promotes the sustainable development of sweet potato protein and peptide.